254 Simulation Matrix: Using Virtual Reality to Help Medical Students Transition into Clinical Practice During COVID-19. (28th February 2022) - Sudin, E.; Hiddema, L.; Bahri, S.; Khin-Htun, S.Y.; Kythreotis, N.; Coughlin, T.
Abstract: Aim: The COVID-19 pandemic has greatly impacted on undergraduate surgical education, as traditional teaching methods have been compromised leading to hesitancy and anxiety amongst medical students. This project provided an alternative teaching method using virtual reality (VR) headsets reducing the impact of the restrictions caused by COVID-19. Method: 23 medical students were enrolled. Clinical scenarios were randomly allocated. Each student completed pre- and post-session questionnaires. Student anxiety and mental preparedness were assessed using a 5-point Likert scale. Paired t-tests were used to analyse impact, and one-sample t-tests were used to assess student perceptions of VR. Results are presented as mean and 95% confidence intervals. Results: VR simulations were found to have significantly increased clinical confidence in managing acutely unwell patients (0.91±0.39 points; p<0.0001) and improved mental preparedness to work in clinical setting (0.52±0.48 points; p=0.036). Our study also showed that VR simulation reduced students' anxiety in managing acutely unwell patients (0.78±0.43 points; p=0.0011). 95.7% students strongly agreed that VR provides a psychologically safe training environment, and overall agreement was highly significant (mean score: 4.96±0.09, p<0.0001). 91.3% strongly agreed that VR training is a useful tool to help mental preparation for transition into clinical practice, and overall agreement was highly significant (mean score: 4.87±0.19, p<0.0001). Conclusions: VR simulation can significantly improve student experience of, and mental preparedness, for transitioning into clinical practice. We would advocate regular use of VR headsets within the rapidly evolving world of surgical education.